A Case Review for the Design of VR-based Training for Enhancing Empathy and Cultural Competency of Public Librarians - Lee, Jisue; Hollister, Jonathan Michael; Lim, Taehyeong; Kim, Kukhyeon; Ryu, Jeeheon (International Journal of Knowledge Content Development & Technology, 2022)
The importance of cultural diversity and competency in library services has been gradually increasing along with rapid growth of international residents (3.3% of total population) in South Korea. Along with a multicultural population, marginalized communities including disabled persons, financially disadvantaged persons, and seniors over 65 years old are growing. To fulfill the South Korean government’s goal of becoming an Innovative Inclusive Nation, public libraries and librarians need to better prepare for these significant changes and work to become more socially inclusive. While librarians need to continuously promote cultural competence, empathy, communication and other critical skills through their professional development training, studies show that little of such training exists in South Korea. In this study, we review related literature and analyze three example cases of Virtual Reality (VR) simulations developed for service-oriented professions, nurses, dentists, and teachers, for the purposes of providing core foundations and best practices to guide the design and development of training programs for pre- and in-service librarians. In the midst of an ongoing pandemic, and the advent of the metaverse and Fourth Industrial Revolution, VR-based, online and mixed face-to-face professional development are likely to become more in demand and will help librarians to become future ready and socially inclusive.